Variation of endosymbiont and citrus tristeza virus (CTV) titers in the Huanglongbing insect vector, Diaphorina citri, on CTV-infected plants - Cui, Xiaoqing; Liu, Yangyang; Zhang, Jingtian; Hu, Panpan; Zheng, Zheng; Deng, Xiaoling; Xu, Meirong (Frontiers in Microbiology, 2023)
Candidatus Liberibacter asiaticus" (CLas) is a notorious agent that causes citrus Huanglongbing (HLB), which is transmitted by Diaphorina citri (D. citri). We recently found that the acquisition and transmission of CLas by D. citri was facilitated by Citrus tristeza virus (CTV), a widely distributed virus in the field. In this study, we further studied whether different CTV strains manipulate the host preference of D. citri, and whether endosymbionts variation is related to CTV strains in D. citri. The results showed that the non-viruliferous D. citri preferred to select the shoots infected with CTV, without strain differences was observed in the selection. However, the viruliferous D. citri prefered to select the mixed strain that is similar to the field's. Furthermore, D. citri effectively acquired the CTV within 2-12 h depending on the strains of the virus. The persistence period of CTV in D. citri was longer than 24 days, without reduction of the CTV titers being observed. These results provide a foundation for understanding the transmission mode of D. citri on CTV. During the process of CTV acquisition and persistence, the titers of main endosymbionts in D. citri showed similar variation trend, but their relative titers were different at different time points. The titers of the "Candidatus Profftella armatura" and CTV tended to be positively correlated, and the titers of Wolbachia and "Candidatus Carsonella ruddii" were mostly negatively related with titers of CT31. These results showed the relationship among D. citri, endosymbionts, and CTV and provided useful information for further research on the interactions between D. citri and CLas, which may benefit the development of approaches for the prevention of CLas transmission and control of citrus HLB.